2008
DOI: 10.1253/circj.72.463
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Delayed Endothelization With Overlapping Drug-Eluting Stents in a Porcine Model of In-Stent Restenosis

Abstract: iffuse, long coronary lesions are associated with an increased rate of restenosis and poor outcome, despite the development of percutaneous coronary intervention (PCI) techniques. [1][2][3] In particular, the implantation of multiple, overlapping, bare metal stents (BMS) has a high restenosis rate. 4,5 Use of drug-eluting stents (DES) results in a significant and sustained suppression of neointimal proliferation, and has greatly attenuated the relationship between stent length and restenosis rate. As a result,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 27 publications
3
42
0
Order By: Relevance
“…23,24 Additionally, autopsy studies have identified the presence of bare struts as a more robust morphological predictor for the occurrence of thrombosis in first-generation DES. 25 The present study with sequential OCT, despite not showing bare struts, did provide images that indicate disCussion Several studies in animal models and previous clinical trials showed delayed endothelialisation of DES when compared to BMS, [21][22][23] and observed the frequent presence of struts covered by thin layers of neointimal tissue, with a thickness well below the limits of detection by intracoronary ultrasound. This delayed heterogeneity in the healing process after 28 days.…”
Section: Resultssupporting
confidence: 47%
“…23,24 Additionally, autopsy studies have identified the presence of bare struts as a more robust morphological predictor for the occurrence of thrombosis in first-generation DES. 25 The present study with sequential OCT, despite not showing bare struts, did provide images that indicate disCussion Several studies in animal models and previous clinical trials showed delayed endothelialisation of DES when compared to BMS, [21][22][23] and observed the frequent presence of struts covered by thin layers of neointimal tissue, with a thickness well below the limits of detection by intracoronary ultrasound. This delayed heterogeneity in the healing process after 28 days.…”
Section: Resultssupporting
confidence: 47%
“…The presence of PLIA might reflect a difference between DES and BMS for arterial healing. 5 According to previous studies, extracellular matrix remodeling plays an essential role in neointimal formation and excessive matrix formation is a determinant of failure of radiation therapy. 6,7 Our findings are in accordance with those reports, showing greater neointimal proliferation in stents with PLIA than in stents without PLIA, for both DES and BMS.…”
Section: Peri-strut Low Intensity Area On Octmentioning
confidence: 99%
“…Inflammation has been associated with impaired endothelialization or higher restenosis rates after the use or paclitaxel or 32 P-containing stents [58, 59]. Gliotoxin also has direct actions on the endothelium, reducing the expression of NF-ĸB-dependent adhesion molecules and leukocyte adhesion in activated cultured endothelial cells.…”
Section: Discussionmentioning
confidence: 99%